Implementasi Undang-Undang Keselamatan dan Kesehatan Kerja Terhadap Buruh Yang Mengalami Cacat Permanen Akibat Kecelakaan Kerja - Damiri, Damiri; Setiady, Tri; Santoso, Imam Budi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
Work accidents often occur in industry due to worker negligence, work equipment or unsafe workplaces, where work accidents can directly harm the company or its employees if the accident results in permanent disability or long-term illness. Therefore, the government has taken concrete steps to ensure that all employees working in companies operating in Indonesia are safe at work by issuing Occupational Health and Safety Regulations (K3) which must be implemented by all companies operating in Indonesia. unchanged. Because work safety is a top priority, implementing this system is one of the absolute requirements that companies must fulfill to obtain an operating permit. It also serves as a check for the government to ensure that all companies comply with the system. However, there are still companies that ignore this obligation, which ultimately results in work accidents. This article is about Giri's brother, a worker working at PT Produkt Raya Industri (HRI) in Walahar Village, Klari District, Karawang Regency, who was terminated unilaterally due to a work accident which resulted in the loss of 4 jaws. Implementation of K3